Photoelectrochemical water splitting with tailored TiO2/SrTiO3@g-C3N4 heterostructure nanorod in photoelectrochemical cell - Bashiri, R. (Elsevier Ltd, 2018)
Solar hydrogen production through water photosplitting in photoelectrochemical (PEC) cell is one of the most desirable, cost-effective and environmentally friendly processes. However, it is still suffering from the low photoconversion efficiency. A novel tailored TiO2/SrTiO3@g-C3N4 heterostructure nanorod was synthesized to investigate the photocatalytic hydrogen production under visible light condition in glycerol-based PEC cell. A series of TiO2 and TiO2/SrTiO3 nanorod were grown on F-doped SnO2 glass (FTO) substrate by hydrothermal method and then were modified using graphitic carbon nitride g-C3N4 via the chemical bath deposition technique. The samples were characterized using X-ray diffraction (XRD), field-emission scanning electron microscopy (FESEM), high-resolution transmission electron microscopy (HRTEM), diffuse reflectance UVâVis spectroscopy (DR-UVâVis), and Fourier transform infrared (FTIR) to explore the physicochemical properties of the prepared photocatalysts. The prepared TiO2/SrTiO3@g-C3N4 served as the efficient photoanode with maximum produced hydrogen of 73 Î¼mol/cm2 compared to others. This photocatalyst had more uniformed structures and shifted more absorbance to the visible region as presented in FESEM and DR-UVâVis. Therefore, high performance of this photocatalyst can be ascribed to the close interfacial connections between g-C3N4 and TiO2/SrTiO3 where the photo-generated electron and holes were effectively separated. Â© 2018 Elsevier B.V.